Tools for precast wall panel installation / Muhammad Shamim Ahmad Laili - Ahmad Laili, Muhammad Shamim (2019)
Project in Malaysia already used IBS system and precast wall panel are most of it. Some size of precast wall panel might need a prop to install it. Prop that usually used in the industry might takes time on the process and kind difficult that can make delay of the work. Hence, to find a way to improve the process of installation of prop on the precast wall panel and slab a research are conducted. This study has were using desk study to collect the data.